Floating-Harbor Syndrome - J Gordon Millichap (Pediatric Neurology Briefs)
Six unrelated children with a unique association of short stature, dysmorphic features, and speech delay are reported from the Harbor/Univ of California at Los Angeles Med Center, the Kennedy Memorial Hospital, Boston, the Beilinson Med Center, the District General Hospital, Stanford, England, and the Cedars-Sinai Med Cntr, Univ of California, LA.